In vivo Assembly in Escherichia coli of Transformation Vectors for Plastid Genome Engineering - Wu, Yuyong; You, Lili; Li, Shengchun; Ma, Meiqi; Wu, Mengting; Ma, Lixin; Bock, Ralph; Chang, Ling; Zhang, Jiang (Frontiers in Plant Science, 2017)
Plastid transformation for the expression of recombinant proteins and entire metabolic pathways has become a promising tool for plant biotechnology. However, large-scale application of this technology has been hindered by some technical bottlenecks, including lack of routine transformation protocols for agronomically important crop plants like rice or maize. Currently, there are no standard or commercial plastid transformation vectors available for the scientific community. Construction of a plastid transformation vector usually requires tedious and time-consuming cloning steps. In this study, we describe the adoption of an in vivo Escherichia coli cloning (iVEC) technology to quickly assemble a plastid transformation vector. The method enables simple and seamless build-up of a complete plastid transformation vector from five DNA fragments in a single step. The vector assembled for demonstration purposes contains an enhanced green fluorescent protein (GFP) expression cassette, in which the gfp transgene is driven by the tobacco plastid ribosomal RNA operon promoter fused to the 5’ untranslated region (UTR) from gene10 of bacteriophage T7 and the transcript-stabilizing 3’UTR from the E. coli ribosomal RNA operon rrnB. Successful transformation of the tobacco plastid genome was verified by Southern blot analysis and seed assays. High-level expression of the GFP reporter in the transplastomic plants was visualized by confocal microscopy and Coomassie staining, and GFP accumulation was approximately 9% of the total soluble protein. The iVEC method represents a simple and efficient approach for construction of plastid transformation vector, and offers great potential for the assembly of increasingly complex vectors for synthetic biology applications in plastids.